The Physical Nature of the Off-center Extended Emission Associated with the Little Red Dots - Chang-Hao Chen; Luis C. Ho; Ruancun Li; Kohei Inayoshi (The Astrophysical Journal Letters)
A significant fraction of little red dots (LRDs) exhibit nearby extended emission of unknown origin. If physically associated with the LRD, this component may trace stellar emission from an off-center host galaxy, neighboring companions, or nebular gas illuminated by the active nucleus. We investigate the detailed spectral energy distribution (SED) of the extended emission near four LRDs in the JWST UNCOVER and MegaScience surveys. We accurately decompose the extended emission from the dominant point source by simultaneously fitting the images in eight broadband and nine medium-band filters. After considering both the results from photometric redshift fitting and the probability of galaxies at different redshifts overlapping, we confirm that the off-center blobs in three sources are physically associated with the LRDs, with two of them showing strong [O iii ] λλ 4959, 5007 emission captured by the medium-band filters. While the SEDs of all three blobs can be modeled assuming star-forming galaxies with stellar mass ∼10 ^8 M _⊙ , the exceptionally strong [O iii ] emission of two sources is best interpreted as pure nebular emission from low-density ( n  < 10 cm ^−3 ), low-metallicity ( Z  ≈ 0.05−1 Z _⊙ ) gas photoionized by the ultraviolet radiation from the nearby LRD. Adopting LRD halo masses constrained by clustering measurements and theoretical considerations, we estimate a typical baryonic halo mass accretion rate of ∼2−9 M _⊙ yr ^−1 . If the halo accretion rate is sustained to z = 4 and stars form with an efficiency of 10%, the accreted gas would build a galaxy with stellar mass ∼10 ^9 M _⊙ , potentially rendering them spatially resolved at lower redshift.